2016
DOI: 10.1097/md.0000000000002619
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Degree of Exercise Tolerance in Children After Surgical Treatment of Complex Cardiac Defects, Assessed Using Ergospirometry and the Level of Brain Natriuretic Peptide

Abstract: Children who underwent surgery for complex congenital heart defects present worse exercise capacity than their healthy peers. In adults and adolescents, heart failure is assessed on the basis of clinical symptoms using the New York Heart Association (NYHA) score, while in an infant Ross scale; heart failure can also be evaluated by other parameters. The purpose of this study was to compare the degree of exercise tolerance in children after surgery for complex heart defects, assessed by the ratio of maximum oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Among the studies, the CHD sample size ranged from 12 ( 30 ) to 496 ( 21 ). Age varied from 7.7 ± 1.7 ( 28 ) to 14 ± 2.72 ( 20 ). The majority of the studies included only complex CHD ( 18 20 , 22 , 25 , 27 , 31 , 33 36 , 38 ), and nine studies included both simple and complex CHD ( 21 24 , 26 , 28 30 , 32 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the studies, the CHD sample size ranged from 12 ( 30 ) to 496 ( 21 ). Age varied from 7.7 ± 1.7 ( 28 ) to 14 ± 2.72 ( 20 ). The majority of the studies included only complex CHD ( 18 20 , 22 , 25 , 27 , 31 , 33 36 , 38 ), and nine studies included both simple and complex CHD ( 21 24 , 26 , 28 30 , 32 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Age varied from 7.7 ± 1.7 ( 28 ) to 14 ± 2.72 ( 20 ). The majority of the studies included only complex CHD ( 18 20 , 22 , 25 , 27 , 31 , 33 36 , 38 ), and nine studies included both simple and complex CHD ( 21 24 , 26 , 28 30 , 32 , 37 ). Sixteen studies included only repaired CHD ( 18 20 , 22 , 24 27 , 30 , 31 , 33 38 ); however, only ten studies reported the age of surgery, which was before 3 years old in the majority of the cases ( 19 , 22 , 26 28 , 30 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After performing a cardiac defect correction procedure, it is important to provide information on hygiene, food (8)(9) , physical activities (10)(11) and others, which may still raise doubts for children's caregivers. To enhance positive responses in child care, educational practices are suggested, with the insertion of concepts of health promotion and empowerment of families of children with heart disease (6)(7)(12)(13) .…”
Section: Introductionmentioning
confidence: 99%